Protein Engineering of a Germacrene A Synthase From Lactuca sativa and Its Application in High Productivity of Germacrene A in Escherichia coli - Chen, Rong; Liu, Yuheng; Chen, Shu; Wang, Ming; Zhu, Yao; Hu, Tianyuan; Wei, Qiuhui; Yin, Xiaopu; Xie, Tian (Frontiers in Plant Science, 2022)
Germacrene A (GA) is a key intermediate for the synthesis of medicinal active compounds, especially for β-elemene, which is a broad-spectrum anticancer drug. The production of sufficient GA in the microbial platform is vital for the precursors supply of active compounds. In this study, Escherichia coli BL21 Star (DE3) was used as the host and cultivated in SBMSN medium, obtaining a highest yield of FPP. The GA synthase from Lactuca sativa (LTC2) exhibited the highest level of GA production. Secondly, two residues involved in product release (T410 and T392) were substituted with Ser and Ala, respectively, responsible for relatively higher activities. Next, substitution of selected residues S243 with Asn caused an increase in activity. Furthermore, I364K-T410S and T392A-T410S were created by combination with the beneficial mutation, and they demonstrated dramatically enhanced titers with 1.90-fold and per-cell productivity with 5.44-fold, respectively. Finally, the production titer of GA reached 126.4 mg/L, and the highest productivity was 7.02 mg/L.h by the I364K-T410S mutant in a shake-flask batch culture after fermentation for 18 h. To our knowledge, the productivity of the I364K-T410S mutant is the highest level ever reported. These results highlight a promising method for the industrial production of GA in E. coli, and lay a foundation for pathway reconstruction and the production of valuable natural sesquiterpenes.